2022
DOI: 10.3390/ijms23042053
|View full text |Cite
|
Sign up to set email alerts
|

SALL4 Oncogenic Function in Cancers: Mechanisms and Therapeutic Relevance

Abstract: SALL4, a member of the SALL family, is an embryonic stem cell regulator involved in self-renewal and pluripotency. Recently, SALL4 overexpression was found in malignant cancers, including lung cancer, hepatocellular carcinoma, breast cancer, gastric cancer, colorectal cancer, osteosarcoma, acute myeloid leukemia, ovarian cancer, and glioma. This review updates recent advances of our knowledge of the biology of SALL4 with a focus on its mechanisms and regulatory functions in tumors and human hematopoiesis. SALL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 211 publications
(284 reference statements)
1
33
0
Order By: Relevance
“…In recent years molecular targeted therapy for cancer has attracted a great deal of attention in order to achieve the goals of precision medicine. The functional association of SALL4 with cancer incidence, progression, and metastasis suggests that SALL4-targeting could be effective in eradicating cancer cells [ 85 ]. However, transcription factors (TFs) historically have been viewed to be “undrugable”, and multiple issues should be considered in designing efficient therapeutics.…”
Section: Sall4 As a Potential Therapeutic Targetmentioning
confidence: 99%
“…In recent years molecular targeted therapy for cancer has attracted a great deal of attention in order to achieve the goals of precision medicine. The functional association of SALL4 with cancer incidence, progression, and metastasis suggests that SALL4-targeting could be effective in eradicating cancer cells [ 85 ]. However, transcription factors (TFs) historically have been viewed to be “undrugable”, and multiple issues should be considered in designing efficient therapeutics.…”
Section: Sall4 As a Potential Therapeutic Targetmentioning
confidence: 99%
“…Any abnormal expression or mutation in this gene leads to the progression of various diseases and the development of different cancers [ 10 ]. In recent years, SALL4 has emerged as a potential biomarker in many cancers, including BC [ 11 , 12 , 13 , 14 ]. Researchers have observed that 86.1% of BC cases have shown high SALL4 expression, and it is regulating different tumor suppressor genes, including E-cadherin (CDH1) and PTEN [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salt‐like transcription factor 4 (SALL4) is a regulator of embryonic stem cells involved in self‐renewal and pluripotency 5 . SALL4 is a novel cancer target, 6 and has been studied in different tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Salt-like transcription factor 4 (SALL4) is a regulator of embryonic stem cells involved in self-renewal and pluripotency. 5 SALL4 is a novel cancer target, 6 and has been studied in different tumors. For example, SALL4 was increased in breast cancer, and its upregulation was associated with regulating cell growth, invasion and apoptosis.…”
Section: Introductionmentioning
confidence: 99%